Cardiovascular risk factors and complications in patients with systemic lupus erythematosus with and without nephritis: a systematic review and meta-analysis - Tak Mao Chan; Danting Zhang; Desmond Y H Yap; Cheuk Yin Wong; Becky M Y Ma; Wynn Cheung (Lupus Science and Medicine)
Introduction It remains unclear how the presence of renal involvement will affect the cardiovascular (CV) risk factors and complications in patients with SLE.Methods We conducted a systematic review and meta-analysis using PubMed, EMBASE, MEDLINE and Scopus to identify studies published between 1947 and 2022 that evaluate the CV risk factors and complications in patients with SLE with or without lupus nephritis (LN).Results 58 studies were evaluated, with 22 two-arm studies (n=8675) included in two-arm meta-analysis and 45 studies (n=385 315) included in proportional meta-analysis. Patients with SLE with LN showed significantly higher risk of hypertension (HT) (OR=4.93, 95% CI=3.17 to 7.65, p<0.00001, I2=56%), hyperlipidaemia (OR=11.03, 95% CI=4.20 to 28.95, p<0.00001, I2=0%) and diabetes mellitus (DM) (OR=1.88, 95% CI=1.09 to 3.25, p=0.02, I2=32%) compared with those without LN. Patients with LN showed numerically higher prevalence of myocardial infarction (OR=1.35, 95% CI=0.53 to 3.45, p=0.52, I2=78%) and cerebrovascular accident (OR=1.64, 95% CI=0.79 to 3.39, p=0.27, I2=23%) than general patients with SLE. The incidence rates of CV mortality are also increased in patients with SLE with LN compared with those without LN (11.7/1000 patient-years vs 3.6/1000 patient-years).Conclusion Patients with SLE with LN show increased risk of CV risk factors including DM, HT and hyperlipidaemia. Early identification and optimal control of these CV risk factors may reduce the risk of CV disease and other non-CV complications.PROSPERO registration number CRD42022314682.